Consumer recommendations for enhancing the Safewards model and interventions. (23rd January 2019) - Kennedy, Hamilton; Roper, Cath; Randall, Rory; Pintado, Daniel; Buchanan‐Hagen, Sally; Fletcher, Justine; Hamilton, Bridget
Abstract: This paper critiques the Safewards model through the lens of lived experiences of psychiatric hospitalization, diagnosis of mental illness, and distress. Special focus is given to the model's tested 10 interventions and to five lesser known interventions, identifying the impact they can have on hospitalized consumers. We highlight the role and prevalence of trauma, as well as the need to prevent harm in hospital settings. We draw upon notions of hospital as a sanctuary for people and the importance of providing a safe ward. 'Sanctuary harm' and 'Sanctuary trauma' are thus defined, with emphasis placed on the Safewards interventions as means by which sanctuary can be achieved. Finally, the consumer‐perspective authors propose expansions to the model, critiquing the defining literature and moving towards a consumer experience of safety that is beyond the model's original intention: to reduce seclusion and restraint practices. Throughout the paper, the term 'consumer' is used in this context to mean people who have experienced or are experiencing psychiatric inpatient care.